“Should We Just Burn It All Down?”: Slowness and Institutional Barriers to a Critical Future in Archives - Wilson, Josh (Archivaria, 2025)
Drawing on data from semi-structured interviews with five archivists, this article explores the barriers to implementing critical practices in archives. It examines if and how archivists use critical practices and approaches to change archival institutions, highlights the barriers they encounter when trying to transform these institutions, and expands archival scholarship on slowness and neoliberalism. Due to archives’ neoliberal entanglements and their slow pace of change, this research data underscores the powerlessness some archivists feel regarding their ability to change the workings of archival institutions. This article shows that creativity, outlined as experimentation and imagination, can provide a bridge between ideas of critical archival studies and particular contexts of practice and conveys some archivists’ view that transforming practice is unfortunately and necessarily slow. Slowness structures the types of responses and critical practices in archival institutions, setting the parameters for what transformations are available. Slowness provides an opportunity for archivists to reflect on the best way to implement practices but also limits the formation of liberatory praxis in institutional archives.